Holistic perspective on the development of elite athletes - Wylleman, P.; Rosier, N. (Sport and exercise psychology research: From theory to practice, 2016)
As the topic of career transitions established itself into a well-established domain of sport psychology, the focus of research evolved from psychological factors influencing athletic retirement to the current developmental and holistic perspective on transitions faced by talented and elite athletes. This chapter opens with a brief overview of sport psychology research into the concept of career transitions. Using the Holistic Athletic Career (HAC) model, the influence of three transitional challenges athletes may face at different points in their career is then described. Finally, the chapter concludes with perspectives for future research on career transitions faced by talented, elite, and retiring athletes as well as possible links to the provision of applied sport psychology services. (übern.)